2014
DOI: 10.1105/tpc.113.121269
|View full text |Cite
|
Sign up to set email alerts
|

The Synaptonemal Complex Protein ZYP1 Is Required for Imposition of Meiotic Crossovers in Barley

Abstract: In many cereal crops, meiotic crossovers predominantly occur toward the ends of chromosomes and 30 to 50% of genes rarely recombine. This limits the exploitation of genetic variation by plant breeding. Previous reports demonstrate that chiasma frequency can be manipulated in plants by depletion of the synaptonemal complex protein ZIPPER1 (ZYP1) but conflict as to the direction of change, with fewer chiasmata reported in Arabidopsis thaliana and more crossovers reported for rice (Oryza sativa). Here, we use RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 57 publications
3
87
0
Order By: Relevance
“…Slides were first blocked for 30 min in 3% bovine serum albumin in 19PBS, 0.1% Triton TM X-100 and then incubated in the primary antibody solution which consisted of one or multiple antibodies (raised in rabbit or rat) diluted in blocking solution in a wet chamber for 1 h at room temperature followed by 24-48 h at 4°C. The antibodies that have been previously described were; anti-AtASY1, -AtZYP1, -HvMLH3, -AtRAD51, -AtMHS4 and -AtDMC1 (Higgins et al, 2012;Phillips et al, 2012Phillips et al, , 2013Barakate et al, 2014). We also prepared a new barley antibody, anti-HvZYP1 (Rat), from an immunization with two individual peptides (Dundee Cell Products, Dundee, UK) to confirm the ZYP1 phenotype.…”
Section: Immunocytologymentioning
confidence: 99%
See 1 more Smart Citation
“…Slides were first blocked for 30 min in 3% bovine serum albumin in 19PBS, 0.1% Triton TM X-100 and then incubated in the primary antibody solution which consisted of one or multiple antibodies (raised in rabbit or rat) diluted in blocking solution in a wet chamber for 1 h at room temperature followed by 24-48 h at 4°C. The antibodies that have been previously described were; anti-AtASY1, -AtZYP1, -HvMLH3, -AtRAD51, -AtMHS4 and -AtDMC1 (Higgins et al, 2012;Phillips et al, 2012Phillips et al, , 2013Barakate et al, 2014). We also prepared a new barley antibody, anti-HvZYP1 (Rat), from an immunization with two individual peptides (Dundee Cell Products, Dundee, UK) to confirm the ZYP1 phenotype.…”
Section: Immunocytologymentioning
confidence: 99%
“…Although much of our current understanding has been developed in small genome models, it is now being extended to large and complex genome nonmodel crops such as barley, where recent cytogenetic studies have described meiotic progression and the chronology of meiotic events (Higgins et al, 2012;Phillips et al, 2012;Barakate et al, 2014). Although largely conforming to expectations, specific observations such as the clustering of the telomeres and the spatiotemporal organization of the recombination machinery reveal that barley differs from Arabidopsis (Armstrong et al, 2001;Higgins et al, 2012;Phillips et al, 2012;Barakate et al, 2014). Even in related grasses (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, by partial RNA interference of the SC component and calculative analysis of the cytological markers, a similar conclusion was reached in the model organism C. elegans (Libuda et al, 2013). However, as C. elegans controls CO designation in a distinct way, it is likely that the role of SC might not be universal among organisms (Barakate et al, 2014). Additionally, as cytological results do not necessarily accord with genetic data (Libuda et al, 2013), it remains unknown whether mutation of the central element of the SC would increase the frequency of M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 3 genetic recombination, which is important for agricultural breeding.…”
mentioning
confidence: 75%
“…However, in most organisms, the number of genetic recombinations is tightly constrained, which hampers the introgression of new genetic traits and limits genetic variation during agricultural breeding (Barakate et al, 2014). Therefore, the possibility of increasing genetic recombination frequency has attracted much interest from crop breeders because of the obvious practical applications in traditional breeding (Crismani et al, 2012;Leflon et al, 2010).…”
mentioning
confidence: 99%
“…However, large-scale proteome studies have shown that translation repression is important in gametogenesis. Nevertheless, proteins involved in the development of meiosis have been identified in different organisms [Sánchez-Morán et al, 2005;Scaife et al, 2010;Wang et al, 2012;Gan et al, 2013;Barakate et al, 2014;Kronjaa et al, 2014]. Although proteome profiles of meiotic cells reveal the number and types of proteins present in different stages of meiosis, dissection of the molecular mechanisms underlying the transition through the complex events of the meiotic process requires the use of gene mutants or RNAi-mediated gene silencing [Roeder, 1997;Cnudde and Gerats, 2005;Namekawa et al, 2005;Neale and Keeney, 2006;San Filippo et al, 2008;Bhalla and Dernburg 2008;Osman et al, 2011;Bolcun-Filas and Schimenti, 2012;Luo et al, 2014;Mercier et al, 2015].…”
Section: Different Approaches In the Study Of Meiosismentioning
confidence: 99%